2018
DOI: 10.14196/mjiri.32.61
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oral contraceptive pills on rheumatoid arthritis disease activity in women: A randomized clinical trial

Abstract: Background: Rheumatoid arthritis is one of the most common autoimmune diseases. Because immunological changes can be induced by steroid hormones, it seems that oral contraceptive pills can affect the severity of the disease. In this study, we examined the effect of oral contraceptive pills on rheumatoid arthritis activity in women. Methods: This blinded randomized clinical control trial was performed in the selected rheumatology centers in Tehran, Iran, in 2011. A total of 100 women with rheumatoid arthritis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The effect of OCs was more pronounced on the DAS28 score; current users of OCs had significantly low DAS28 scores in comparison to past users and both of them had a lower score when compared with non-users. Our findings agree with Amini et al who found that the activity and severity of rheumatoid arthritis can be improved by oral contraceptive pills [30]. Also, Brouwer et al reported that oral contraceptives are considered the best option for RA patients as they positively affect the disease activity [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The effect of OCs was more pronounced on the DAS28 score; current users of OCs had significantly low DAS28 scores in comparison to past users and both of them had a lower score when compared with non-users. Our findings agree with Amini et al who found that the activity and severity of rheumatoid arthritis can be improved by oral contraceptive pills [30]. Also, Brouwer et al reported that oral contraceptives are considered the best option for RA patients as they positively affect the disease activity [31].…”
Section: Discussionsupporting
confidence: 92%
“…Fayed et al found that RA patients who are using combined oral contraceptives have the lowest disease severity in comparison to the other methods of contraception [32]. However, using OCs did not have any significant effect on ESR; this agrees with Amini et al [30], and it also had no significant effect on ACPA and RF titers in all studied groups.…”
Section: Discussionsupporting
confidence: 57%
“…These identified factors can induce anti-RA drug resistance, as seen with methotrexate, naproxen, dexamethasone, and other anti-RA drugs. [5][6][7][8] Experimental and clinical studies show that the dysregulation of sex hormones influences immune reactivity in RA patients. These hormonal and immunological perturbations contribute to the influx of more lymphocytes and monocytes in the synovial fluids of female individuals than in their male counterparts and higher antigen-presenting activity and mitogenic responses.…”
Section: Impact Statementmentioning
confidence: 99%
“…Exogenous hormone use in the form of oral contraceptives (OC) has been previously linked to the development and progression of several immune-mediated diseases, such as Crohn's disease [1,2], rheumatoid arthritis [3], and systemic lupus erythematosus [4][5][6]. Nevertheless, the exact mechanism underlying these observations has not been fully established.…”
Section: Introductionmentioning
confidence: 99%